KEMAMPUAN MENGELOLA KONFLIK INTERPERSONAL DI TEMPAT KERJA DITINJAU DARI PERSEPSI TERHADAP KOMUNIKASI INTERPERSONAL DAN TIPE KEPRIBADIAN EKSTROVERT - Dewi, Tyas Hapsari; Handayani, Agustin (Jurnal Psikologi, 2013)
This study aims to determine the relationship between perceptions of interpersonal communication and extrovert personality type with the ability to manage interpersonal conflict in the workplace on employees Editorial Suara Merdeka Semarang. The sample in this study was 60 employees. Major hypothesis in this study is that there is a relationship between perceptions of interpersonal communication and extrovert personality types with the ability to manage interpersonal conflict in the workplace. Minor hypotheses in this study were 1) There is a positive relationship between perceptions of interpersonal communication with the ability to manage interpersonal conflict in the workplace, 2) There is a positive relationship between the extroverted personality type with the ability to manage interpersonal conflict in the workplace. Major hypothesis testing using regression analysis two predictors, the results obtained ry (1-2) = 0.639 with p = 0.000 (p <0,01). The first minor hypothesis testing using the partial correlation technique with variable controlling extrovert personality type, the results obtained ry(1-2) = 0.609 with p = 0.000 (p <0,01). The second minor hypothesis testing using the partial correlation technique with variable controlling perceptions of interpersonal communication, the results obtained ry(2-1) = -0, 069 with p = 0.605 (p> 0,05).